2012
DOI: 10.4314/wsa.v38i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a protocol for selection and prioritisation of organic contaminants in the drinking water value chain: Case study of Rand Water, South Africa

Abstract: Approaches that prioritise chemicals according to their importance as environmental contaminants have been developed by government agencies and private industries. However, it has been noticed that few approaches, such as one published by the United States Environmental Protection Agency (USEPA), address the needs of the drinking water industry. There is also no generic approach to the selection, prioritisation and monitoring of organic contaminants in the drinking water value chain. To safeguard drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…For example, the veterinary use of diclofenac, which is also a human pharmaceutical used as an anti-inflammatory treatment, was found to be responsible for the massive decline in populations of vulture species in certain areas of Asia 7 ; ethinylestradiol, one of the active ingredients in the contraceptive pill, has been associated with endocrine disruption and feminisation in fish 8 ; and there is concern that long-term exposure to antibiotic pharmaceuticals and disinfectant products may be contributing to the selection of resistant bacteria with significant impacts upon human health. 9 In South Africa, Ncube et al 10 suggested a protocol for the selection and prioritisation of contaminants in drinking water. Patterton 11 surveyed seven cities in South Africa and showed the presence of 32 compounds in drinking water, predominantly pharmaceuticals and pesticides, including carbamazepine (anticonvulsant), phenytoin (antiepileptic) and diclofenac.…”
Section: Background To the Studymentioning
confidence: 99%
“…For example, the veterinary use of diclofenac, which is also a human pharmaceutical used as an anti-inflammatory treatment, was found to be responsible for the massive decline in populations of vulture species in certain areas of Asia 7 ; ethinylestradiol, one of the active ingredients in the contraceptive pill, has been associated with endocrine disruption and feminisation in fish 8 ; and there is concern that long-term exposure to antibiotic pharmaceuticals and disinfectant products may be contributing to the selection of resistant bacteria with significant impacts upon human health. 9 In South Africa, Ncube et al 10 suggested a protocol for the selection and prioritisation of contaminants in drinking water. Patterton 11 surveyed seven cities in South Africa and showed the presence of 32 compounds in drinking water, predominantly pharmaceuticals and pesticides, including carbamazepine (anticonvulsant), phenytoin (antiepileptic) and diclofenac.…”
Section: Background To the Studymentioning
confidence: 99%
“…However, it is increasingly becoming known that several types of PPCPs are also accumulating in water systems to the same extent as contraceptive medications. These compounds can serve as EDCs and are not completely removed during water treatment (Ncube et al, 2012). From these contaminants, pharmaceuticals stand out as one of the sources which might potentially cause endocrine-disrupting activities in non-target organisms.…”
Section: Pharmaceuticals and Steroid Hormones Detected In South Africmentioning
confidence: 99%
“…There have been reports of DDT bioaccumulation in wildlife and humans since the late 1960s ( Van Dyk et al 1982 ; Wassermann et al 1970 ). Further monitoring has also revealed persistent organic pollutants (POPs), PAHs, PBDEs, polychlorinated biphenyls (PCBs), perfluorooctane sulfonate (PFOS), phenols, heavy metals such as cadmium and lead, phthalates, and bisphenol A (BPA) in African waters ( Ncube et al 2012 ; Olujimi et al 2010 ) and in animal tissues ( du Preez et al 2016 ; Nieuwoudt et al 2009 ; Nieuwoudt et al 2011 ; Polder et al 2008 ; van der Schyff et al 2016 ; Quinn et al 2009 ; Bornman et al 2010b ). The first report of endocrine disruption in a fish species in Africa involved intersex in the African catfish, Clarias gariepinus , inhabiting water sources contaminated with the estrogenic compound p -nonylphenol ( p -NP), possibly from upstream activites of industries, agriculture, informal settlements, and municipal treatment plants ( Barnhoorn et al 2004 ).…”
Section: Edc Exposures: Impact On Wildlife Health In Africamentioning
confidence: 99%